Promoting Equity and Inclusion through Public Policy: Strategies for Addressing Systemic Discrimination and Inequality - Syafril, Muh (Journal of Public Representative and Society Provision, 2021)
This study aims to explore strategies for addressing systemic discrimination and inequality through public policy, with a focus on promoting equity and inclusion. The research examines the effectiveness of various policies, such as progressive taxation, minimum wage legislation, healthcare access, and affirmative action programs, in reducing societal inequality. The methodology employed includes both qualitative and quantitative approaches. Qualitative data were gathered through semi-structured interviews, while quantitative data were collected via an online survey involving 500 participants. The results reveal significant patterns in social media use, digital activism, and their impacts on mental health and social behavior. Through case studies, the research demonstrates how successful policies can foster greater social mobility and create more inclusive societies. The study concludes that comprehensive public policy interventions are crucial in eradicating institutionalized discrimination and advancing social justice.